Ankle desarthrodesis: report of three cases - Soares Baumfeld, Tiago; Marinho Guimarães, Beatriz; de Souza Nery, Caio Augusto; Soares Baumfeld, Daniel (Journal of the Foot & Ankle, 2022)
The good results of primary ankle arthroplasty and long-term dissatisfaction with arthrodesis have made arthrodesis, that is, the conversion of an arthrodesis into arthroplasty, an option for patients with a painful ankle fusion. This study presents the results of three patients submitted to ankle desarthrodesis in Brazil between 2019 and 2021. Two men and one woman, aged between 48 and 52 years and with an arthrodesis prosthetic interval between two and 30 years, presented satisfactory results after arthroplasty. Pain reduction and increased functional capacity were observed, representing an improvement in the visual analog scale (VAS) between 5 and 6 points, range of motion (ROM) gain between 20Åã and 45Åã and progress in the American Orthopaedic Foot & Ankle Society (AOFAS) score between 17 and 54 points in the postoperative follow-up. Although it is a procedure with a long learning curve, desarthrodesis should be considered a therapeutic alternative to painful ankle arthrodesis. Level of Evidence IV; Case Series; Therapeutic Studies - investigating the results of treatment.